PENINGKATAN HASIL BELAJAR SISWA DALAM MATERI PELAJARAN MAWARIS MELALUI PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL DENGAN PROYEK DI KELAS XII IPA 1 SMA NEGERI 1 KEPENUHAN - Makmur Makmur (STKIP ROKANIA, 2020)
The purpose of this study is to determine the acceleration of the achievement of basic competencies XII class student SMA Negeri 1 Kepenuhan 2018/2019 school year at Mawaris material through the implementation of the Education Unit Level Curriculum (KTSP) with CTL models in the project. The subjects were high school students in Negeri 1 Medan class XII IPA-1 consisted of 14 male students and 23 female students. Research undertaken in three cycles, first cycle two meetings, one meeting cycle II and III of one cycle of meetings, with each cycle consisting of planning, action, observation, and reflection. Success indication is the attainment of the objectives of this study in accordance with the allocation of time available in the research, to discuss material that is shown with a minimum score of exhaustiveness of LKS is 84.50, a minimum score of exhaustiveness of learning outcomes is the average value of 70.00 and exhaustiveness grade class is 80%, and increased activity of students and teachers are shown by the percentage of activity of students and teachers in learning more than 70%. The result of research shows the average score LKS at cycle I 72.97, cycle II 86.48, and cycle III 94.59. the average result of student learning at cycle I 69.59 with completely score in the class 78.37%, cycle II 78.35 with completely score in class 86.50%, cycle III 84 with completely score in class 92%, and finally result 81.16 with 35 students have complete score. The students activities at cycle I 70%, cycle II 75%, and cycle III 85%. At cycle III, the mastery of standard competency has achieve the succesfull indicator needed. Teacher activities of cycle I 60.71%, cycle II 82.15%, and cycle III 91.07%.